PERILAKU MASYRAKAT MENGGUNAKAN JASA GOCAR DI KOTA DENPASAR - Putra Jaya, Kris Cahyadi; Rahanatha, Gede Bayu (E-Jurnal Manajemen; Vol 9 No 1 (2020)DO - 10.24843/EJMUNUD.2020.v09.i01.p10, 2020)
The purpose of this study was to determine the behavior in Denpasar City using GoCar services. This research was conducted in Denpasar City. Methods of data collection using surveys with questionnaires and data analysis techniques in this study using multiple linear regression analysis techniques. The results of this study found that the Perceived Value, Perceived Risk and Perceived Quality had a positive and significant influence on the intention to use GoCar services. Perceived Price and Advertising have a positive and significant effect on the intention to use GoCar services. Consumer attitudes have a positive and significant influence on the intention to use GoCar services. GoJek company in this case GoCar should begin to increase brand awareness of its products and start educating prospective customers that GoCar products are safe to use. Keywords: consumer attitudes, services, services, perceived value